On the basis of inclusivity determining gender-inclusive spaces within fitness centers in Davao City, Philippines - Seo, Jeslaine Shane G. (2023)
The fitness service market in the Philippines is expanding and seeing tight competition. However, users, regardless of gender, noted that the hyper-masculinization of fitness spaces made them uncomfortable to use and occasionally inaccessible. With that, this study aimed to look at spatial factors that could affect the inclusiveness of fitness centers for men, women, and gender-diverse people. A survey with 60 respondents was conducted specifically in selected fitness centers of Davao City. Descriptive and Thematic Analyses were used to assess the perception of men, women, and gender-diverse people on gender inclusivity and their perception of the servicescapes of fitness centers which helped the author establish design guidelines for a gender-inclusive fitness facility. It was found in this study that gender inclusivity can be achieved when designers are able to address the 4 themes namely; Free from Discrimination, Judgement, and Harassment, Safety and Comfort, Free to express oneself, and Caters to everyone's needs. Servicescape factors such as Accessibility, Equipment Condition, Facility Layout, Facility System, and Social Factor were found to be the top factors that encourage users in utilizing fitness centers.Keywords: Davao City; fitness centers; health and wellness; gender inclusivity; servicescapes